KEMITRAAN INDONESIA AUSTRALIA MELALUI PROGRAM KOMPAK DALAM UPAYA PENGEMBANGAN UMKM UNTUK MEMBANTU MENGURANGI KEMISKINAN DI KABUPATEN PACITAN TAHUN 2017-2019 - Eka Fadhilah Santoso (2021)
This study discusses the partnership between Indonesia and Australia in helping to reduce poverty in Indonesia by developing the local economy through MSME activities with a market intermediary approach. Australia sees that the stable economy in Indonesia is still unable to prosper all the people because of the uneven distribution of economic development. Therefore, Australia has partnered with Indonesia through the Kompak program in an effort to help reduce poverty in Indonesia. This study has a problem formulation "How is the implementation of the Indonesia-Australia partnership program through Kompak in developing MSMEs to help reduce poverty in Pacitan Regency in 2017-2019?". This study aims to find out the partnership through the development of MSMEs in helping reduce poverty between Indonesia and Australia. The method used by the author is descriptive qualitative, namely a research method that describes as well as explains the events that occurred from various data collected in the form of interviews and through secondary data. The use of this method aims to explain more deeply about the implementation and forms of cooperation in local economic development through MSMEs. In this study, the author uses the concepts of bilateral cooperation, national interest, and paradiplomacy to analyze the partnership between Indonesia and Australia through the Kompak program. Based on the analysis of the data from this study, it was concluded that the partnership between Indonesia and Australia through the Kompak program, namely MSME development activities with a market intermediary approach, was successful in helping improve the economy of the community in Pacitan Regency. However, in the process of implementing this program, there are still obstacles where there is a lack of commitment from the stakeholders involved in implementing this program. In addition, it was found that in this partnership both Indonesia and Australia have their respective interests to reduce poverty as well as the interests of "good international citizenship". Keywords: Partnership, Poverty, Economic Development, Kompak.